Repetitive Transcranial Magnetic Stimulation Ameliorates Cognitive Impairment by Enhancing Neurogenesis and Suppressing Apoptosis in the Hippocampus in Rats with Ischemic Stroke - Guo, Feng; Lou, Jicheng; Han, Xiaohua; Deng, Yuguo; Huang, Xiaolin (Frontiers in Physiology, 2017)
Cognitive impairment is a serious mental deficit caused by stroke that can severely affect the quality of a survivor’s life. Repetitive transcranial magnetic stimulation (rTMS) is a well-known rehabilitation modality that has been reported to exert neuroprotective effects after cerebral ischemic injury. In the present study, we evaluated the therapeutic efficacy of rTMS against post-stroke cognitive impairment (PSCI) and investigated the mechanisms underlying its effects in a middle cerebral artery occlusion (MCAO) rat model. The results showed that rTMS ameliorated cognitive deficits and tended to reduce the sizes of cerebral lesions. In addition, rTMS significantly improved cognitive function via a mechanism involving increased neurogenesis and decreased apoptosis in the ipsilateral hippocampus. Moreover, brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin-related kinase B (TrkB), were clearly upregulated in ischemic hippocampi after treatment with rTMS. Additionally, further studies demonstrated that rTMS markedly enhanced the expression of the apoptosis-related B cell lymphoma/leukemia gene 2 (Bcl-2) and decreased the expression of the Bcl-2-associated protein X (Bax) and the number of TUNEL-positive cells in the ischemic hippocampus. Both protein levels and mRNA levels were investigated. Our findings suggest that after ischemic stroke, treatment with rTMS promoted the functional recovery of cognitive impairments by inhibiting apoptosis and enhancing neurogenesis in the hippocampus and that this mechanism might be mediated by the BDNF signaling pathway.